Mengelola Konflik Peran Pribadi dan Profesional: Studi Kualitatif tentang Work-Life Balance pada Mahasiswa Profesi Kedokteran - Syafitri Chandilla Umasugi; Mirwan Surya Perdhana (Diponegoro Journal of Management, 2026)
Medical professional education is an intensive training phase with high academic and clinical demands, increasing the risk of work-life balance imbalance and burnout. This phenomenon not only reflects individual health issues but also represents a strategic issue in human resource management in healthcare organizations. Medical professional students, as strategic human capital, play a crucial role in the quality of service and the sustainability of teaching hospitals. However, previous research has been dominated by quantitative approaches and focused on individual aspects, resulting in limited understanding of students' subjective experiences within the context of organizational policies, supervision, and work culture.This study aims to explore medical professional students' experiences of work-life balance from the perspective of human resource management and organizational behavior. The study used a qualitative approach through in-depth interviews, with thematic analysis referring to the concepts of role conflict, job demands-resources, and perceived organizational support.The results indicate that role conflict and role strain are influenced by work design, clinical workload, supervision systems, and organizational culture. Institutional support as part of HRM practices is still perceived as limited. This research confirms that work-life balance is an organizational behavior issue that requires ongoing HRM policy intervention.